Report of the Interregional Seminar on the Training of Professional and Voluntary Youth Leaders : Organized Jointly by the United Nations, the United Nations Educational, Scientific and Cultural Organization and the Government of Denmark - United Nations, New York, NY. (Washington, D.C. : Distributed by ERIC Clearinghouse, 1970)
The Interregional Seminar on the Training of Professional and Voluntary Youth Leaders was held in Holte, Denmark, from 7 to 22 October 1969. The purpose of the seminar was to review the current experience of both governmental and non-governmental services responsible for training youth leaders for various types of work. The seminar considered the training of professional and voluntary youth leaders under three main headings: (1) objectives of training for professional and voluntary leaders; (2) policies for training youth workers and improving their status; and (3) organization, content and methods of current training programs. The first part of the report discusses these three areas, and contains concluding comments. Part Two contains Background Papers, as follows: I. Summary of the Country Papers; II. The Training of Young People for Action in Community Development; III. Need for Constant Reappraisal and Research in Regard to the Training of Youth Leaders; IV. The Training of Professional and Voluntary Youth Leaders; V. The Training of Youth Leaders; and VI. International Youth Organizations and the Training of Professional and Voluntary Youth Leaders. An annex provides a list of participants. (DB)
Availability: United Nations, New York, N.Y. Sales No.: E.70.II.H.4 (U.S. $2.00).
Microfiche.
Keywords: Educational Programs; Human Services; International Programs; Leadership Training; Professional Personnel; Seminars; Training Objectives; Volunteers; Youth Leaders; Youth Programs; Denmark -- United Nations